(untitled) (Homoeopathy for All, 2022)
Varicose Veins is one of the major ailments of lower limbs.Varicose veins can be explained as a disorder of the veins (especially of legs) due to the backward flow and turbulence in the circulation of the blood. The veins get perverted, become torturous. The disease also shows many associated symptoms which worsens the condition of the varicose veins. Varicose veins are seen globally and influenced by activity and lifestyle. The present article deals with brief introduction regarding the etiopathogenesis of varicose veins, related causes and symptoms, and the homoeopathic remedies which useful in curing the varicose veins.